2019
DOI: 10.1093/mnras/stz2707
|View full text |Cite
|
Sign up to set email alerts
|

X-shooter observations of strong H2-bearing DLAs at high redshift

Abstract: We present results from spectroscopic observations with X-shooter at the Very Large Telescope of seven H 2 -bearing DLAs at high redshifts (z abs ∼ 2.5 − 3). These DLAs were originally selected from the presence of strong H 2 lines directly seen at the DLA redshift in low-resolution, low S/N SDSS spectra. We confirm the detection of molecular hydrogen in all of them. We measure the column densities of H i, H 2 in various rotational levels, and metal species, and associated dust extinction. The metallicities, o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 79 publications
11
50
0
Order By: Relevance
“…the technique, see, e.g., Balashev et al 2019). We find that the total neutral-hydrogen column density is log N(H i) = 21.37 ± 0.01 centered on z abs = 2.811379(20) in agreement with the value reported by Ledoux et al (2006)…”
Section: Componentsupporting
confidence: 87%
See 3 more Smart Citations
“…the technique, see, e.g., Balashev et al 2019). We find that the total neutral-hydrogen column density is log N(H i) = 21.37 ± 0.01 centered on z abs = 2.811379(20) in agreement with the value reported by Ledoux et al (2006)…”
Section: Componentsupporting
confidence: 87%
“…One can see that the UV flux in both components of the DLA towards Q 0528−250, as well as the thermal pressure (shown by inclined dashed lines in the figure), are higher than the average of other H 2 -bearing DLAs. Balashev et al (2017Balashev et al ( , 2019 also reported tentative evidence of an increase of thermal pressure with increasing hydrogen column density. This suggests that high H i column-density systems have smaller impact parameters than typical DLAs and hence probe the inner regions of galaxies where the thermal pressure may be enhanced by high UV flux.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Fortunately, in many cases the metallicity can be well constrained using the associated metal lines. Additionally, the number density and UV flux also can be estimated for some absorption systems from associated finestructure levels of C i and rotational levels of H2 (Balashev et al 2019). In Fig.…”
Section: Discussionmentioning
confidence: 99%